2022
DOI: 10.1186/s12877-022-03538-x
|View full text |Cite
|
Sign up to set email alerts
|

Inequity in the healthcare utilization among latent classes of elderly people with chronic diseases and decomposition analysis in China

Abstract: Background Studies have shown chronic disease-based healthcare utilization inequity is common. Hence, exploring this issue can help in establishing targeted measures and protecting the rights and interests of vulnerable groups. Against this background, the purpose of this study is to explore the latent classification of elderly patients with chronic disease and compare healthcare utilization inequity among latent classes. Methods This study used th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…Previous studies also identified higher health inequality in western China in comparison with eastern and central China 5 70. The rapid urbanisation process in China has been accompanied with large scales of internal migration, which led to the serious polarisation in underdeveloped areas, resulting in increased ‘left behind’ children and elderly in China 71 72. Overall, however, regional and urban–rural disparities have now played a less significant role in inequality of HRQoL than others: their contributions to CI do not exceed 3.00% according to the findings of our current study.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies also identified higher health inequality in western China in comparison with eastern and central China 5 70. The rapid urbanisation process in China has been accompanied with large scales of internal migration, which led to the serious polarisation in underdeveloped areas, resulting in increased ‘left behind’ children and elderly in China 71 72. Overall, however, regional and urban–rural disparities have now played a less significant role in inequality of HRQoL than others: their contributions to CI do not exceed 3.00% according to the findings of our current study.…”
Section: Discussionsupporting
confidence: 63%
“…[ 41 ] Another study revealed 5 latent classes based on 14 chronic conditions in a representative sample of older adults with at least 1 chronic disease in China, including the musculoskeletal system (19.91%), hypertension (10.36%), respiratory system (12.91%), digestive system (12.39%), and cardiovascular system (44.3%). [ 36 ] In addition, intervertebral disc disease, a locally prevalent chronic condition, was included and analyzed, which has not been covered in the literature. Multimorbidity patterns vary according to age group, region, and objective.…”
Section: Discussionmentioning
confidence: 99%
“…Five latent classes were identified based on 14 chronic conditions of the China Health and Retirement Longitudinal Study in 2018, including musculoskeletal system, hypertension, respiratory system, digestive system, and cardiovascular system. [ 36 ] This study was conducted using LCA to identify the multimorbidity patterns.…”
Section: Introductionmentioning
confidence: 99%
“…By conducting longitudinal comparative analysis, Fu(2020) found that there was a certain degree of inequity in IHSU for middle-aged and elderly patients with chronic diseases, and per capita family consumption expenditure and basic insurance for urban employees alleviated this inequality [21]. Zhao(2022) pointed out that inequalities of medical utilization in elderly patients with chronic diseases still exists, and the speci c performances of inequity vary among latent classes [22]. Currently, scholars have found that inequalities of healthcare utilization varies according to which chronic disease patient suffer, including the types and numbers of diseases.…”
Section: Introductionmentioning
confidence: 99%